A SENSITIVE SPECTROPHOTOMETRIC METHOD FOR TRACE AMOUNTS DETERMINATION OF PROMETHAZINE IN DRUG FORMULATIONS VIA ION PAIR COMPLEX FORMATION - Al-Rufaie, Mohauman Mohammad Majeed (Malaysian Journal of Science, 2021)
ABSTRACT This paper discusses a quick and easy spectrophotometric approach for the estimation of promethazine HCl drug in a pure and pharmaceutical formulation. This system relies on the instruction of colour ion-pair between complexes. Promethazine HCl is reacted in acidic medium with methyl blue dye resulting in the formulation of a coloured product with a maximum absorption of 480 nm. In order to increase the sensitivity of the system, parameters of the reaction conditions were studied and optimised. Beer's law was applied on all the concentrations of 2.0 â€“ 100.0 Î¼g/ml, with 1.420 Î¼g/ml and 6.088Ã— 104 l/mol.cm as detection limit and molar absorptivity respectively. After plotting the calibration graph, the method's precision was checked and it was found the values were within the accurate range. The impact of widespread interferences on the current approach was examined. The method was utilised to estimate promethazine HCl in various pharmaceutical products available with fine recoveries in the market.